Aeromagnetic surveying using a simulated unmanned aircraft system. (21st October 2013) - Caron, Raymond M.; Samson, Claire; Straznicky, Paul; Ferguson, Stephen; Sander, Luise
ABSTRACT Carleton University and Sander Geophysics are developing an unmanned aircraft system (UAS) for aeromagnetic surveying. As an early indication of the expected performance of the unmanned aircraft system, a simulated unmanned aircraft system (sUAS) was built. The simulated unmanned aircraft system is a T‐shaped structure configured as a horizontal gradiometer with two cesium magnetometers spaced 4.67 m apart, which is the same sensor geometry as planned for the unmanned aircraft system. The simulated unmanned aircraft system is flown suspended beneath a helicopter. An 8.5 km2 area in the Central Metasedimentary Belt of the Grenville Province, near Plevna, Ontario, Canada, was surveyed with the simulated unmanned aircraft system suspended 50 m above ground. The survey site was chosen on the basis of its complex geological structure. The total magnetic intensity (TMI) data recorded were compared to that obtained during a conventional fixed‐wing survey and a ground survey. Transverse magneto‐gradiometric data were also recorded by the simulated unmanned aircraft system. The simulated unmanned aircraft system total magnetic intensity data have a higher resolution than the conventional fixed‐wing data and were found to have a similar resolution to that of the ground survey data. The advantages of surveying with the simulated unmanned aircraft system were: (1) the acquisition of a detailed data set free of gaps in coverage at a low altitude above the terrain and (2) substantial saving of time and effort. In the survey site, the 4.67 m simulated unmanned aircraft system gradiometer measured the transverse magnetic gradient reliably up to an altitude of 150 m above ground.